IMPLEMENTASI ELECTRONIC CUSTOMER RELATIONSHIP MANAGEMENT UNTUK MENINGKATKAN KEPUASAN DAN LAYANAN KEPADA PELANGGAN THANI COFFEE - Setyawan, Ivan; Hin, Lauw Li; Anubhakti, Dian; Gata, Grace (Universitas Budi Luhur, 2024)
Customer support and satisfaction are very important in running a Coffee shop business. Thani Coffee as a place to relax and enjoy Coffee if there is work or college assignments. Thani Coffee has issues, particularly the offerings in keeping relationships with clients, consisting of useless providers for customers when placing orders, in addition to facts about drink promos that are less powerful so that occasionally Thani Coffee workers neglect to provide statistics about drinks that may be on promo to customers, and a less powerful complaint and tips submission center so that Thani Coffee is difficult to improve services. Based on the current problems, this research uses a buyer relationship control (CRM) method approach where there is 1 CRM stage, namely Enhance. The method in this observation uses direct observation, interviews and also conducts documentation. The e-CRM device created using the Hypertext Preprocessor programming language and MySQL as its database. This system was created with the aim of providing service and pleasure to Thani Coffee customers, which has a variety of features for customers, drink promo features, ordering, reduction, complaints and instructions, drink reviews. The features that can be used by Thani Coffee are menu input, cut price, order data, customer data, sales report generation, user reports, criticism and review reports as well as providing facilities to change banners to assist beverage promo activities. The research conclusion is to facilitate the sale and recapitulation of Thani Coffee sales and also to compete with other Coffee Shops.